An update on the efficacy of endobronchial valve therapy in the management of hyperinflation in patients with chronic obstructive pulmonary disease. (December 2015) - Valipour, Arschang; Burghuber, Otto Chris
Lung volume reduction surgery has been shown to be effective in patients with heterogeneous emphysema, but is also associated with a relatively high perioperative morbidity and mortality. Accordingly, several novel and potentially less invasive methods for bronchoscopic lung volume reduction have been developed. Endobronchial valve (EBV) therapy is one such therapeutic approach in patients with advanced emphysema. It has been the most widely studied technique over the past years and represents an effective treatment option for patients with severe heterogeneous upper- or lower-lobe-predominant emphysema. The choice of EBV therapy largely depends on the distribution of emphysema and the presence or absence of interlobar collateral ventilation. Adequate patient selection and technical success of valve implantation with the intention of lobar exclusion are predictive factors for positive outcomes. This review attempts to highlight the milestones in the development of bronchoscopic lung volume reduction with one-way valve implantation over the past few years.